PROTECTION OF CHILDREN'S RIGHTS TO SUFFICIENCY AND MAINTENANCE: A Normative Legal Analysis of Government Policy in Indonesia - Ahmad Najib Afandi; Ismatul Maula; Ahmad Rezy Meidina; Achmad Siddiq; Mohammad Irsyad (PT Taskuliah Edukasi Indonesia, 2025)
This study examines Islamic family law policies concerning child protection in Indonesia, with a specific focus on the regulation of child financial support and maintenance obligations. Islamic law provides comprehensive normative guidance on family welfare and parental responsibility; however, gaps often emerge at the level of legal implementation. Using a normative juridical approach, this study analyzes secondary legal materials, including statutory regulations such as the Marriage Law and the Compilation of Islamic Law, as well as relevant legal doctrines and court decisions. The findings reveal several concrete weaknesses in the implementation of child support obligations, including the absence of effective enforcement mechanisms against non-compliant parents, limited judicial consistency in determining the amount and continuity of maintenance, and the marginalization of children’s financial rights in post-divorce disputes. These weaknesses result in recurrent violations of children’s rights to adequate financial support, particularly in cases involving divorce and economic vulnerability. This study underscores the necessity of strengthening normative clarity, judicial enforcement, and legal awareness to ensure comprehensive and effective protection of children’s financial rights within Indonesia’s Islamic family law framework. [Studi ini mengkaji kebijakan hukum keluarga Islam terkait perlindungan anak di Indonesia, dengan fokus khusus pada regulasi dukungan finansial dan kewajiban pemeliharaan anak. Hukum Islam memberikan panduan normatif yang komprehensif mengenai kesejahteraan keluarga dan tanggung jawab orang tua; namun, celah sering muncul pada tingkat implementasi hukum. Menggunakan pendekatan juridis normatif, studi ini menganalisis bahan hukum sekunder, termasuk peraturan perundang-undangan seperti Undang-Undang Perkawinan dan Kompilasi Hukum Islam, serta doktrin hukum yang relevan dan putusan pengadilan. Temuan menunjukkan beberapa kelemahan konkret dalam implementasi kewajiban dukungan finansial anak, termasuk ketidakhadiran mekanisme penegakan hukum yang efektif terhadap orang tua yang tidak patuh, ketidakkonsistenan yudisial dalam menentukan jumlah dan kelangsungan pemeliharaan, serta marginalisasi hak finansial anak dalam sengketa pasca-cerai. Kelemahan ini mengakibatkan pelanggaran berulang terhadap hak anak untuk mendapatkan dukungan finansial yang memadai, terutama dalam kasus perceraian dan kerentanan ekonomi. Studi ini menekankan pentingnya memperkuat kejelasan normatif, penegakan hukum, dan kesadaran hukum untuk memastikan perlindungan komprehensif dan efektif terhadap hak-hak finansial anak dalam kerangka hukum keluarga Islam Indonesia.]